PERSEPSI KEHARMONISAN KELUARGA TERHADAP KECENDERUNGAN KENAKALAN REMAJA DI DESA TANJUNG RAMAN KECAMATAN PENDOPO KABUPATEN EMPAT LAWANG - Indah Pusnita (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2021)
The study with the title: Perceptions of Family Harmony Against Juvenile Delinquency Tendencies in Tanjung Raman Village, Pendopo District, Empat Lawang Regency. Social problems that are categorized as deviant behavior include juvenile delinquency. To find out about the background of juvenile delinquency, it can be done through two approaches, namely an individual approach and a systems approach. In the individual approach, the individual is the unit of observation as well as the source of the problem. For the systems approach, the individual is the unit of observation while the system is the source of the problem. Based on the research conducted, it was found that there was a negative relationship between juvenile delinquency and family functioning. This means that the increasing social functioning of a family in carrying out life's tasks, roles and functions, the lower the children's level of delinquency or the lower the quality of the delinquency. In addition, the use of free time that is not directed is a very dominant cause for adolescents to perform deviant behavior.